Dual-Operation Regime Thulium-Doped Fiber Laser and Its Applications in Cascaded Raman Light and Supercontinuum Generation - Zhijian Zheng; Deqin Ouyang; Junqing Zhao; Peiguang Yan; Jinzhang Wang; Shenghua Lin; Shuangchen Ruan (IEEE Photonics Journal)
We report on a passively mode-locked thulium-doped fiber laser (TDFL) with dual operation regimes and applications in cascaded Raman light and supercontinuum generation. The mode-locking is initiated by using a semiconductor saturable absorber mirror (SESAM) and can operate at both fundamental mode-locking and noise-like twin-pulse regimes. Output power can be scaled up through two-stage amplifications, and then was further fed into a segment of ultrahigh numerical aperture (NA) single-mode fiber with a length of ∼30 m. At the fundamental mode-locking regime, two orders of stokes lights can be generated, centered at 2.13 and 2.35 μm, respectively, with a maximum total power of 3.75 W. At the noise-like twin-pulse regime, a near-infrared supercontinuum from 1.93 to 2.46 μm was generated with a maximum average output power of 2.5 W. It is, to the best of our knowledge, the first demonstration of both cascaded Raman light and supercontinuum generation with the same system.